Anti-biofilm efficacy of green-synthesized ZnO nanoparticles on oral biofilm: In vitro and in silico study - Lahiri, Dibyajit; Ray, Rina Rani; Sarkar, Tanmay; Upadhye, Vijay Jagdish; Ghosh, Sujay; Pandit, Soumya; Pati, Siddhartha; Edinur, Hisham Atan; Abdul Kari, Zulhisyam; Nag, Moupriya; Ahmad Mohd Zain, Muhammad Rajaei (Frontiers in Microbiology, 2022)
The development of biofilm on the biotic and abiotic surfaces has been a greatest challenge for health care sectors. At present times oral infection has been a common concern among people with unhealthy life style and most of these biofilms associated infections are resistant to antibiotics. This has increased a search for the development of alternate therapeutics for eradicating the biofilm associated infection. Nanobiotechnology being an effective way to combat such oral infections may encourage use of herbal compounds as bio reducing and capping agents. Green-synthesis of ZnO nanoparticles (ZnO NP) by the use of the floral extract of Clitoria ternatea, a traditionally used medicinal plant, showed stability for a longer period of time. The NPs as depicted by TEM image with a size of 10 nm showed an excitation spectra at 360 nm were found to remain stable for a considerable period of time. It was observed that the NPs were effective in the eradication of the oral biofilm formed by the major tooth attacking bacterial strains namely Porphyromonsas gingivalis and Alcaligenes faecalis, through bringing about considerable reduction in the extracellular polymeric substances (EPS) It was observed that the viability of the Porphyromonsas gingivalis and Alcaligenes faecalis was reduced by NP treatment to 87.89±0.25% in comparison to that of amoxicillin. The results went in agreement with the findings of modelling performed by the use of response surface methodology (RSM) and artificial neural network (ANN). The microscopic studies and FT-IR analysis revealed that there was considerable reduction in the biofilm after NP treatment. The In-silico studies further confirmed that the ZnO NPs showed considerable interactions with the biofilm forming protein. Hence the study showed the ZnO NPs derived from Clitoria ternatea can be used as an effective alternative therapeutic for the treatment of biofilm associated oral infection.